Chitin-Chitosan Myriad Functionalities in Science and Technology - Sukhadeorao Dongre, Rajendra (IntechOpen, 2018)
Chitin is the second most abundant biopolymer after cellulose and is a resourceful copious and cheap biomaterial discovered in 1859 owing to significant industrial and technological utility. Raw chitin-chitosan resembles keratin in its biological functions. Chitin chemistry vastly developed via innate unparalleled biological features and exceptional physicochemical characters. Chitosan endures assorted chemical/physical modifications easily at free proactive functionalities, yet intact bulk properties are achieved through processing, viz., film, membrane, composite, hybrid, nanofibre, nanoparticle, hydrogel and scaffolds. Rapidly lessen bioresources signify chitosan as an option due to renewable eco-friendliness and drive embryonic myriad applications in S&T. Controlled surface modification in its flexible framework imparts advanced functionalized applications in science and technology developments. Chitosan-matrix is advantageous over biopolymers due to inherent economic, versatile and unequivocal portfolio from bio-molecule to quantum dots which traced its great journey in modern S&T. Overall, chitosan chemistry boosted R&D in countless domains like agriculture, biochemical, medicine, pharmaceutics, nanotechnology, biotechnology, material/food science, microbiology, biomedicine, bioengineering, biochemistry, bioprocessing and environment.